Beam profile measurements with the 2-D laser-wire - Price, M; Blair, G; Bosco, A; Boorman, G; Carter, J; Agapov, I; Driouichi, C; Boogert, S; Kamps, T; Poirier, F; Balewski, K; Lewin, H; et al. (European Physical Society Accelerator Group (EPS-AG), 2006)
The laser-wire will be an essential diagnostic tool at the International Linear Collider (ILC). It uses a finely focused laser beam to measure the transverse profile of electron bunches by detecting the Compton-scattered photons downstream of the interaction point (IP), where the laser beam intersects the electron beam. Such a system has been installed at the PETRA storage ring at DESY, which uses a piezo-driven mirror to scan the laser-light across the electron beam. This paper reports recent upgrades to the PETRA system, including the implementation of a new laser.